2023
DOI: 10.1038/s41558-022-01584-2
|View full text |Cite
|
Sign up to set email alerts
|

Widespread spring phenology effects on drought recovery of Northern Hemisphere ecosystems

Abstract: The time required for an ecosystem to recover from severe drought is a key component of ecological resilience. The phenology effects on drought recovery are, however, poorly understood. These effects centre on how phenology variations impact biophysical feedbacks, vegetation growth and, ultimately, recovery itself. Using multiple remotely sensed datasets, we found that more than half of ecosystems in mid- and high-latitudinal Northern Hemisphere failed to recover from extreme droughts within a single growing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 68 publications
3
23
0
Order By: Relevance
“…Similar needs exist for other inferred mediators of ecosystem responses to drought, including a host of biotic, edaphic and climatic modifiers (e.g. Costa et al., 2023; Cusack et al., 2023; Hoover et al., 2014, 2022; Li et al., 2023; Smith et al., 2023).…”
Section: How Can Drought Experiments Be Improved?mentioning
confidence: 90%
See 1 more Smart Citation
“…Similar needs exist for other inferred mediators of ecosystem responses to drought, including a host of biotic, edaphic and climatic modifiers (e.g. Costa et al., 2023; Cusack et al., 2023; Hoover et al., 2014, 2022; Li et al., 2023; Smith et al., 2023).…”
Section: How Can Drought Experiments Be Improved?mentioning
confidence: 90%
“…As noted above, ecosystem responses and sensitivity to drought can vary dramatically, and although fewer experiments have focussed on the recovery of ecosystem functioning post‐drought (Luo, Ma, et al., 2023), both large‐scale observations (Jiao et al., 2021; Li et al., 2023; Petrie et al., 2018; Schwalm et al., 2017; Wu et al., 2018) and past experiments suggest that there is quite significant variability in the recovery of ecosystems post‐drought (e.g. Stuart‐Haëntjens et al., 2018).…”
Section: Looking Forwardmentioning
confidence: 99%
“…The partial correlations between GUD and both precipitation and radiation were opposite in sign (figures 7(c) and (e)), indicating that increased preseason precipitation accompanied by heavy cloud cover may mitigate the impacts of reduced radiation on GUD. In addition, the impacts of drought on GUD changes is also considerable, extreme drought events will cause delaying GUD and the alleviation of drought will cause advancing GUD (Li et al 2023), which is shown by negative correlation between SPEI and GUD in Central Asia and Central east Russia and 6% area with advancing GUD predominated by SPEI changes (figures 7(d) and ( 3)).…”
Section: The Role Of Climatementioning
confidence: 99%
“…Accurately predicting future vegetation growth dynamics and ecosystem evolution is a fundamental scientific challenge within the realm of global change research (Alkama et al., 2022; Y. Zhang et al., 2022). While climate change is a well‐recognized factor, it is equally important to consider the impact of variations in spring phenology on vegetation growth (Y. Li et al., 2023). Therefore, quantifying the relative importance of spring phenology and climate change on vegetation growth can provide a deeper understanding of the driving mechanisms behind vegetation dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…While climate change is a well-recognized factor, it is equally important to consider the impact of variations in spring phenology on vegetation growth (Y. Li et al, 2023). Therefore, quantifying the relative importance of spring phenology and climate change on vegetation growth can provide a deeper understanding of the driving mechanisms behind vegetation dynamics.…”
mentioning
confidence: 99%